Travel, Writing, and the Global Middle Ages. Issue 3 (4th March 2016) - Phillips, Kim M.
Abstract: Travel and mobility were vital aspects of medieval European experience. Historians have long recognised this through studies of migration, exile, everyday journeys and long‐distance voyages as recorded in travellers' reports and narratives. Yet it is only in recent decades that a distinct field of medieval travel writing studies has emerged. This article surveys recent significant contributions to the study of travel literature of the period c. 300 to c. 1500, concentrating on secondary scholarship in English and particularly on works published or reissued since the late 1990s. It considers issues of genre, offers a definition of 'medieval travel writing' and proposes the authorial category of the 'writer‐traveller'. It examines selected recent trends in study of Christian pilgrimage, European travel writing on the wider world and medieval Islamic and Jewish voyage literature. It notes that there has been heightened attention to women and gender, to 'virtual' pilgrimage as Christian devotion, to attempts at cross‐cultural comprehension before the age of European imperialism and to the distinctive perspectives offered by Muslim and Jewish authors. Concluding with suggestions for future directions, including enhanced attention to gender theory and cross‐cultural comparison, it finally argues for the place of travel writing studies in histories of medieval globalism following the global turn.